Macroscopic and microscopic investigation of uranium elimination by Ca–Mg–Al-layered double hydroxide supported nanoscale zero valent iron. Issue 10 (19th September 2018) - Pang, Hongwei; Wu, Yihan; Huang, Shuyi; Ding, Congcong; Li, Shun; Wang, Xiangxue; Yu, Shujun; Chen, Zhongshan; Song, Gang; Wang, Xiangke
Abstract : Ca–Mg–Al-LDH/nZVI nanocomposites showed excellent U(vi ) removal performance from aqueous solutions through the coordination of reduction and adsorption reactions. Abstract : In the past few decades, uranium ( 235, 238 U(vi )) has turned into a forefront environmental issue due to its extensive use in the nuclear industry and its toxicity and radioactivity. Herein, nanoscale zero valent iron (nZVI), which was supported on Ca–Mg–Al-layered double hydroxide (Ca–Mg–Al-LDH/nZVI), was fabricated via an in situ growth route and employed for U(vi ) decontamination from aqueous solutions. Spectroscopy and microscopy (SEM, TEM, FTIR, XRD, BET, and XPS) technologies were applied for the investigation of the properties of Ca–Mg–Al-LDH/nZVI and the U(vi ) elimination mechanism. Ca–Mg–Al-LDH/nZVI had a remarkable BET surface (426.8 m 2 g −1 ), abundant functional groups ( i.e., Fe–O, Al–O, –OH, etc .), high efficiency (4 h to achieve equilibrium) and large adsorption capacities ( Q max = 216.1 mg g −1 ) for U(vi ) removal. The decontamination process of U(vi ) was observed to be pH-dependent and ionic strength-independent, suggesting that the adsorption was predominated by inner-sphere surface coordination. XPS spectroscopy analyses indicated that the reduction and adsorption of nZVI and the adsorption of Ca–Mg–Al-LDH dominated U(vi ) elimination on Ca–Mg–Al-LDH/nZVI. The environmentally friendly synthesis method, excellent physicochemical properties and remarkable removal performance suggested that Ca–Mg–Al-LDH/nZVI was applicable as a potential adsorbent for U(vi ) decontamination from wastewater in environmental pollution remediation.